Civil War in Myanmar. Causes, Actors, Development - Miroslav Nožina (Vojenské rozhledy)
The civil war in Myanmar has been going on for more than seven decades. After the military coup in February 2021, it has undergone significant structural changes and gained new momentum. The causes of the conflict lie in the inability of different ethnic and political groups to find a way to coexist within a single state entity and the autonomisation of the military. The main actors in the war in Myanmar today are the military junta and its supporters, the democratic opposition and ethnic organisations. After the coup, the strength of the resistance movement and its operational capabilities are growing. However, this growth has its limits, given the continued disunity of opposition forces, the technical superiority of the Myanmar army and the strengthening of its numbers through compulsory conscription.